Laparoscopic Splenectomy for Hairy Cell Leukemia in Pregnancy - Adeniji, Beni Adegoke (Hindawi Publishing Corporation, 2010)
Objective. We present a successful case of laparoscopic splenectomy for a massively enlarged spleen at 25 weeks of gestation for hairy cell leukemia in pregnancy in a woman with initial hemoglobin of 4.3 gm/dl and platelet count of 18,000/mm(3). Study Design. Case report. Results. This report provides an approach to management that may be applicable in those cases where thrombocytopenia or other clinical imperatives preclude delaying treatment till after pregnancy. Conclusion. Hairy cell leukemia is a clonal B-Cell malignancy, for which there is very limited experience worldwide for its management when it occurs during pregnancy. Laparoscopic splenectomy should be considered as a therapeutic option, even with a significantly enlarged spleen, in order to avoid the risks of fetal exposure to chemotherapeutic agents. Unique considerations relating to pregnancy are highlighted.